Mathematical Review of the Sukuk-Linked Awqaf Model: A Critical Analysis of Notation Consistency and Formula Validity - Pratama, Jovian Dian (Theoretical and Practical Research in Economic Fields, 2026)
This manuscript provides a critical mathematical review of a Sukuk-Linked Awqaf model with the aim of improving notational consistency, analytical clarity, and economic interpretability. The study focuses on correcting weaknesses arising from inconsistent time indexing, redundant equations, misuse of mathematical symbols, and unclear assumptions regarding asset growth, rental income, construction cost, and revenue sharing. By imposing a consistent growth process for waqaf land value, several artificial discount factors are eliminated and present value expressions are derived directly using standard time value of money principles. Key equalities in the original model are reinterpreted as minimum contractual conditions rather than strict identities to better reflect economic uncertainty. The analysis also introduces explicit decision criteria for all stakeholders - Nadzhir, investors, and state-owned enterprises (SOE) - based on present value comparisons. The revised formulation offers a cleaner and more rigorous mathematical foundation for Sukuk-Linked Awqaf and strengthens its relevance as an instrument of Islamic social finance.